Evaluation of amino acid and fatty acid profile of Pleurotus sapidus-an edible mushroom from India - kaur, balwinder kaur (Mushroom Research, 2019)
Abstract The sporophores of Pleurotus sapidus Quèl raised through cultivation in the laboratory were used for amino acid and fatty acid analyses during the present study. Amino acid composition of dried mushroom sporophore was analyzed by HPLC. A total of 17 amino acids were detected in the mushroom sample. All the essential and non-essential amino acids were documented in the examined sample, of which glutamic acid was predominant. The total amino acid content has been evaluated at 38.36100g-1. The essential amino acid (EAA) index (28.18%) and biological value (BV=18.99%) has also been determined for the examined sample. The analysis of fatty acid composition was performed by gas liquid chromatography coupled to flame ionization detector. Amongst the 14 fatty acids quantified, unsaturated fatty acids and in particular, oleic acid and linoleic acid were predominantly present in the sample.